Investigação do potencial alelopático de Pittosporum undulatum Vent - Carpanezzi, Fernando Bertol (Universidade Federal de São Carlos, 2009)
Pittosporum undulatum Vent., an Australian tree implicated in supression of tree recruiment in many ecosystems, is found invading secondary Araucaria forests in subtropical Brazil. The first chapter of this study aimed to investigate the role of allelopathy in the invasive proccess, accessing germination and growth of Bauhinia forficata Link. in presence of secondary metabolites from cheesewood leaves. Leachates in concentrations of 20%, 15%, 10% and 5% (w/v), extracts from dry material (10%; 7,5%; 5% and 2,5%) and coumarin solutions (2,5 mM; 1,25 mM; 0,625 mM and 0,3125 mM) were prepared. Petri-dishes germination bioassays, with countings done at each 12 hours, allowed to determinate both germinabilty and germination rate; polyethylene glicol (PEG 6000) solutions were used to evaluate osmotic effects. For seedlings growth, the three highest concentrations of each solution were tested and after seven days root and shoot lenght were measured. While germinability was only sensitive to extracts from dry material, the germination rate showed a dose-dependent curve for all solutions. In seedlings, roots were the most sensitive structure and severe morfo-anatomic anomalies were observed. The main purpose of the second chapter was to investigate the use of Pittosporum undulatum Vent. (cheesewood) leaves as a possible sustainable alternative for barnyard grass control. Leachates in concentrations of 20%; 15%; 10%; 5% and 2,5% (w/v), aqueous extracts from powdered leachated and non- eachated leaves (10%; 7,5%; 5%; 2,5% and 1,25%), coumarin solutions (2,5 mM; 1,25 mM; 0,625 mM and 0,3125 mM) and Roundup Original® according to label informations were prepared. Polyethylene glycol were also used. Both germinability and germination rate were determined by germination biossays, with countings done at each 12 hours. In growth experiments, seedlings were exposed for seven days, when root and shoot length were measured. All solutions, with exception of coumarins, caused only small inhibitory effects on germination. In relation to the growth, all treatments but control caused necrose, absence of hairs and dose-dependent lenght reduction in radicles. Hipocotiles were affected by phenolic compound, extracts from non-leachated leaves and gliphosate. Although the allelopathic effects, ecophisiological aspects relative to Pittosporum undulatum still need to be cleared before its leaves can be used as a herbicide.
Assesment of allelopathic potential in cheesewood (Pittosporum undulatum Vent)
Keywords: Ecologia; Alelopatia; Espécies invasoras; Pau-incenso; Pittosporaceae; Extratos aquosos; Allelopathy; Alien invasive species; Aqueous extracts; CIENCIAS BIOLOGICAS::ECOLOGIA